Cover Chem. Eng. Technol. 4/2016. Issue 4 (April 2016) - Unknown
Abstract: Cover: BIOGAS PILOT PLANT at the DBFZ The cover picture shows the biogas pilot plant at the DBFZ (German Biomass Research Center). This extends the range of application‐oriented research being carried out at the DBFZ to enhance process understanding and improve the efficiency of biogas production. The dimensioning of the fermenters allows experiments to be conducted on full scale, thereby ensuring good transferability of results into practice. The facility features two independent lines with identical capacity which can be operated as a single‐ or two‐stage system, with optional hydrolysis. The first line is a wet fermentation system with a main fermenter in the form of a continuous stirred tank reactor with a central agitator. The second line can optionally be run with a main fermenter of identical design or with a plug‐flow fermenter. A post‐digester with a flexible rubber gas dome collects the digestate from both lines and after post digestion, they are carried over to the digestate storage tank. The biogas is used in a 75 kWel combined heat and power unit (CHP) to cover the facility's own energy demand. Surplus power can be fed into the DBFZ grid. For substrate supply, small amounts of self‐produced silage can be stored on site. For a precise measurement of the gas production rate the primary fermenters have solid roofs. Terminal units in the pipeline system and at the gas capture point permit sampling and the installation of additional sensors.